2010
DOI: 10.22146/ijc.21727
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Surfactant and Phenol in Coastal Waters of Jakarta Gulf

Abstract: The investigation of the anionic surfactant and phenol contamination in sea water of Jakarta Gulf was carried out. The sea water samples in Jakarta Gulf were collected in May 2004 at 21 stations (sampling sites). The monitoring results indicated that the anionic surfactants were detected in sea water samples from 20 stations with the low varied level from 0.276 mg/L to 0.779 mg/L. The anionic surfactant at the station 21 was detected with the highest value, it was 1.202 mg/L. The phenol pollutants in sea wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Phenolics were only found at station 3 with levels of 0.014 mg.L-1, thus exceeding the quality standard of 0.002 mg.L-1. Phenols in waters are generally found due to industrial waste disposal and fuel from ships (Mbunde et al, 2018;Winarno et al, 2010). The condition in station 3, located between Ulee Lheue and Lampulo, is possible due to the high activity and traffic of fishing boats.…”
Section: Water Qualitymentioning
confidence: 99%
“…Phenolics were only found at station 3 with levels of 0.014 mg.L-1, thus exceeding the quality standard of 0.002 mg.L-1. Phenols in waters are generally found due to industrial waste disposal and fuel from ships (Mbunde et al, 2018;Winarno et al, 2010). The condition in station 3, located between Ulee Lheue and Lampulo, is possible due to the high activity and traffic of fishing boats.…”
Section: Water Qualitymentioning
confidence: 99%
“…Pencemaran perairan oleh fenol dan turunananya menjadi isu penting yang berkembang dalam beberapa tahun terakhir. Menurut penelitian yang dilakukan Winarno et al (2006), kandungan fenol di beberapa lokasi perairan di Teluk Jakarta sudah melebihi batas ambang yang dijinkan pemerintah, yaitu 0,002 mg/L. Kandungan fenol pada air tanah dangkal pada jarak 1 -375 meter dari TPA Sampah Suwung Kelurahan Pedungan Denpasar sudah tergolong dalam tingkatan tercemar berat, yaitu kandungannya mencapai 17,39 mg/L (Arbain, dkk, 2008).…”
Section: Pendahuluanunclassified
“…The most important nutrient content is actually on trace elements, particularly iodine which ranged from 0.1 to 0.15% of the dry weight (Matanjun, et al, 2008). Vitamin AEucheumacottonii is 59.39 IU / kg (Sunarto, 2003 (Winarno, 1996). Kadir study (2000) showed that the iodine content of juice Eucheumacottonii range of 1.23 ppm to 1.82 ppm, while in the fresh form Eucheumacottonii iodine content was 2.83 ppm.…”
Section: Introductionmentioning
confidence: 99%